2017
DOI: 10.2152/jmi.64.20
|View full text |Cite
|
Sign up to set email alerts
|

Extracts of <i>citrus Sudachi</i> peel attenuate body weight gain in C57BL/6 mice fed a high-fat diet

Abstract: : Citrus Sudachi is the special local product of Tokushima Prefecture, and over 98% % of Sudachi consumed in Japan every year is produced in Tokushima Prefecture. In this study, we evaluated the function of sudachi peel extract (SPE) using an animal model of obesity. C57BL/6 mice were fed a high-fat diet containing 1% % SPE powder. Treatment with SPE significantly decreased body weight compared to that of mice fed a high-fat diet. A significant difference in body weight was observed between the control and SPE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…However, there were no significant differences in total food and calorie intakes between HFDC-LL and HFD-LL mice. Previously, it has been reported that dietary intake of grapefruit (Citrus paradisi) (15), Citrus unshiu (16), Citrus bergamia (17), Cit- rus sunki (18), Citrus sudachi (19), and Citrus junos (20) suppressed body weight, body fat, blood TG, and T-CHO in obese mouse models. These studies showed that hesperidin, neohesperidin, nobiletin, tangeretin, and naringin have critical roles in the effects (15)(16)(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…However, there were no significant differences in total food and calorie intakes between HFDC-LL and HFD-LL mice. Previously, it has been reported that dietary intake of grapefruit (Citrus paradisi) (15), Citrus unshiu (16), Citrus bergamia (17), Cit- rus sunki (18), Citrus sudachi (19), and Citrus junos (20) suppressed body weight, body fat, blood TG, and T-CHO in obese mouse models. These studies showed that hesperidin, neohesperidin, nobiletin, tangeretin, and naringin have critical roles in the effects (15)(16)(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…This extract was rich in phenolic compounds that are known to posses several actions to improve glucose tolerance as reported below. The in vivo reduction of blood glucose and plasma insulin levels was demonstrated for both Citrus reticulata and Citrus sudachi peels extract (Guo et al, 2016;Kobayashi et al, 2017). In particular, Citrus sudachi exerted its effect via reduction of TNF-α mRNA expression.…”
Section: Antibacterial Potentialmentioning
confidence: 95%
“…It has been widely reported that citrus fruit or citrus peel extract has potential antiobesity properties. Previous studies indicate that citrus fruits contain numerous bioactive compounds such as alkaloids, limonoids, phenolic acids, flavanone glycosides, polymethoxylated flavones (PMFs), and its derivatives. Furthermore, Sayuri Inafuku-Teramoto et al reported that immature citrus fruits usually have higher levels of functional phytochemicals (e.g., p -synephrine, flavanone glycosides, and PMFs) than mature fruits. In this study, we found that some major phytochemicals in ICRE are p -synephrine, narirutin, hesperidin, nobiletin, and tangeretin (Table ).…”
Section: Discussionmentioning
confidence: 99%